EARLY YEARS OF INDEPENDENCE IN UZBEKISTAN ENTREPRENEURSHIP IN FERGANA REGION: REFORMS, PROBLEMS, UPDATES - Maroziqov Akmal Abdurashidovich (Scholar Express Journal, 2021)
The article describes the process of building a diversified economy in Uzbekistan in the first years of independence in the conditions of socioeconomic crisis, the creation of a new type of agrarian relations.
Keywords: Property; Collective Farm; State Farm; Farmer